Mathematics Problem-Solving Ability of Elementary School Students in Solving Hots Type of Mathematics Problems - Ike Kurniawati; Mochamad Guntur; Irma Sofiasyari (Journal of Education and Learning Mathematics Research (JELMaR), 2022)
Students should be trained to solve problems in mathematics so that they can do so in their studies also so that they can solve problems in their everyday lives, especially mathematical ones, with ease. This study aimed to learn how well students in grade five at SDN 26 in Rejang Lebong solved mathematical problems requiring higher-level critical thinking (HOTS). This study is an example of content analysis as a type of qualitative descriptive research. Students from Class 26 at VA SDN SDN in Rejang Lebong comprise the research sample. Testing members are used for data collection. The test questions are five multiple-choice HOTS problems. Research findings demonstrate students' varying abilities to solve arithmetic problems. The students have a good grasp of the issues from the perspective of problem understanding. Students aren't fully utilizing concepts and procedures while analyzing problems and developing solutions with mathematical tools, which is an issue with regard to problem-solving planning. Students have not fully written solutions to problems from both the planning and implementation perspectives, and from the perspective of looking back at previous solutions, they have not written those solutions down either.